Marketing Benefits Derived from Clustering: the Case of Vegetable Clusters in Mindanao - Lamban, R.; Montiflor, M.; Rodel, R.; Axalan, J.; Concepcion, S.; Bacus, R.; Apara, D.; Israel, F.; Batt, Peter; Murray-Prior, Roy; Rola-Rubzen, Maria Fay (International Society of Horticultural Science, 2013)
One of the most limiting constraints for improving the profitability of smallholder vegetable farmers is poor marketing. With the lack of knowledge and inability to negotiate with downstream buyers, farmers have little option other than to sell their products to the traditional market. To facilitate access to technical information, credit and institutional markets, smallholder farmers are forming collaborative marketing groups. Clustering is one form of collaborative marketing in which smallholder farmers are organized into small groups within a defined territory or geographic area. Using the CRS Eight Step Plan for Agro-enterprise Development, 29 clusters were formed in three provinces in the Southern Philippines. This study explores the various marketing benefits smallholder farmers have achieved after joining the cluster. After interviewing 61 vegetable farmers from 10 clusters using a structured questionnaire, results show that upon joining the cluster, farmers became more aware of their buyer’s preference for product quality and gained knowledge on how to properly handle and package their produce. Cluster farmers increased their income from vegetable farming by selling a greater product variety, a larger volume and gaining access to high value markets.